Pendekatan Konstruktivisme Dalam Pembelajaran Seni Tari Untuk Meningkatkan Hasil Belajar Siswa - Thahirah, Nida; Budiman, Agus (Jurnal Pendidikan Tari, 2023)
This research examines the use of a constructivist approach in learning dance. The constructivism approach is a learning model that provides students with opportunities to develop their creativity through various activities in educational interactions, which allows them to explore and discover knowledge independently. The aim of this research is to gain a comprehensive understanding of the influence of the constructivist approach on improving the learning outcomes of class XI high school students on the topic of function, type, form and aesthetic value of creative dance. This research method uses a quantitative pre-experimental design approach (One Group Pretest-Posttest). The research subjects were 36 students in one experimental class. The research instrument used consisted of pre-test and post-test questions totaling 15 multiple choice questions with five answer choices, student worksheets accompanied by games related to the material discussed, where the material was different at each meeting as an effort to support the constructivist approach. , learning effectiveness questionnaire using a constructivist approach, and interview questions. The results of this research prove that learning using a constructivist approach can improve student learning outcomes, the results of the analysis of the average assessment before implementation are in the low category, the post-test results through applying the constructivist approach increase the average score in the high category. The results of the questionnaire also showed that the use of a constructivist approach in learning dance received a positive response from students. The percentage score results show that the constructivist approach is effective in improving student learning outcomes and creating a more interesting learning atmosphere, so that students can develop their creativity through educational interactions, explore and discover knowledge independently. Apart from that, the constructivism approach also succeeded in increasing the learning motivation of class XI high school students.